Meningkatkan kemampuan representasi matematis: Model pembelajaran DMR inovatif dengan integrasi media kotak pertanyaan - Widyawati, Santi; Putra, Fredi Ganda; Mufita, Husni (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2024)
This study aimed to scrutinize the effectiveness of the DMR (Diskursus Multy Reprecentacy) model with Question Box media in bolstering the mathematical representation abilities of eighth-grade students. A quasi-experimental design was employed, engaging 96 students selected via Cluster Random Sampling technique. The effectiveness was evaluated by comparing the DMR model against the conventional expository teaching method using a t-test with a 5% significance level. In this research, data testing uses the SPSS application. Findings revealed that the DMR teaching model assisted by the Question Box media was significantly more effective in enhancing students' mathematical representation skills than the traditional expository model. These findings suggest that the integration of the DMR teaching model with Question Box media could serve as an alternative pedagogical strategy in mathematics education to facilitate a deeper understanding of mathematical concepts among students.